The IASLC Mesothelioma Staging Project: Proposals for Revisions of the T Descriptors in the Forthcoming Eighth Edition of the TNM Classification for Pleural Mesothelioma - BATIREL, HASAN FEVZİ (ELSEVIER SCIENCE INC, 2016)
Introduction: The current T component for malignant pleural mesothelioma (MPM) has been predominantly informed by surgical data sets and consensus. The International Association for the Study of Lung Cancer undertook revision of the seventh edition of the staging system for MPM with the goal of developing recommendations for the eighth edition. Methods: Data elements including detailed T descriptors were developed by consensus. Tumor thickness at three pleural levels was also recorded. An electronic data capture system was established to facilitate data submission. Results: A total of 3519 cases were submitted to the database. Of those eligible for T-component analysis, 509 cases had only clinical staging, 836 cases had only surgical staging, and 642 cases had both available. Survival was examined for T categories according to the current seventh edition staging system. There was clear separation between all clinically staged categories except T1a versus T1b (hazard ratio = 0.99, p = 0.95) and T3 versus T4 (hazard ratio = 1.22, p = 0.09), although the numbers of T4 cases were small. Pathological staging failed to demonstrate a survival difference between adjacent categories with the exception of T3 versus T4. Performance improved with collapse of T1a and T1b into a single T1 category; no current descriptors were shifted or eliminated. Tumor thickness and nodular or rindlike morphology were significantly associated with survival. Conclusions: A recommendation to collapse both clinical and pathological T1a and T1b into a T1 classification will be made for the eighth edition staging system. Simple measurement of pleural thickness has prognostic significance and should be examined further with a view to incorporation into future staging. (C) 2016 International Association for the Study of Lung Cancer. Published by Elsevier Inc. All rights reserved.
Keywords: Mesothelioma; Staging; T component; Prospective; MALIGNANT MESOTHELIOMA; F-18-FDG PET/CT; TUMOR THICKNESS; CT SCANS; SURVIVAL; THERAPY; VOLUME; ASSOCIATION; PREDICTION; PARAMETERS